Plasma Efavirenz Exposure, Sex, and Age Predict Virological Response in HIV-Infected African Children. (1st October 2016) - Bienczak, Andrzej; Denti, Paolo; Cook, Adrian; Wiesner, Lubbe; Mulenga, Veronica; Kityo, Cissy; Kekitiinwa, Addy; Gibb, Diana M.; Burger, David; Walker, A. Sarah; McIlleron, Helen
Abstract : Background: Owing to insufficient evidence in children, target plasma concentrations of efavirenz are based on studies in adults. Our analysis aimed to evaluate the pediatric therapeutic thresholds and characterize the determinants of virological suppression in African children. Methods: We analyzed data from 128 African children (aged 1.7–13.5 years) treated with efavirenz, lamivudine, and one among abacavir, stavudine, or zidovudine, and followed up to 36 months. Individual pharmacokinetic (PK) measures [plasma concentration 12 hours after dose (C12h), plasma concentration 24 hours after dose (C24h), and area under the curve (AUC0-24 )] were estimated using population PK modeling. Cox multiple failure regression and multivariable fractional polynomials were used to investigate the risks of unsuppressed viral load associated with efavirenz exposure and other factors among 106 initially treatment-naive children, and likelihood profiling was used to identify the most predictive PK thresholds. Results: The risk of viral load >100 copies per milliliter decreased by 42% for every 2-fold increase in efavirenz mid-dose concentration [95% confidence interval (CI): 23% to 57%; P < 0.001]. The most predictive PK thresholds for increased risk of unsuppressed viral load were C12h 1.12 mg/L [hazard ratio (HR): 6.14; 95% CI: 2.64 to 14.27], C24h 0.65 mg/L (HR: 6.57; 95% CI: 2.86 to 15.10), and AUC0-24 28 mg·h/L (HR: 5.77; 95% CI: 2.28 to 14.58). Children older than 8 years had a more than 10-fold increased risk of virological nonsuppression ( P = 0.005); among children younger than 8 years, boys had a 5.31 times higher risk than girls ( P = 0.007). Central nervous system adverse events were infrequently reported. Conclusions: Our analysis suggests that the minimum target C24h and AUC0-24 could be lowered in children. Our findings should be confirmed in a prospective pediatric trial. Abstract : Supplemental Digital Content is Available in the Text.